Modern grids, old sources: the viability of applying modern typologies of religious diversity to medieval Islamic thought - Kocyigit, Ibrahim (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2025)
This article assesses the viability of applying modern typologies of religious diversity to medieval Islamic thought. Using Alan Race’s threefold schema of exclusivism, inclusivism, and pluralism, as refined by Perry Schmidt-Leukel, it reconstructs these categories in epistemological and soteriological terms. It tests them through a qualitative, text-oriented analysis of key figures in classical Islamic theology (kalam) and Islamic mysticism (taṣawwuf). The study proceeds by clarifying the truth and salvation claims presupposed by each category and examining how medieval arguments about prophetic finality, moral responsibility, divine justice, and mercy align with, or fail to align with, the modern grid. Al-Māturīdī and al-Ghazālī represent ‘moderate exclusivism’, affirming the finality and superiority of Islam while allowing limited salvation for certain religious ‘others’ through appeals to reason and differentiated accountability. Ibn Taymiyya embodies an ‘undecided exclusivism,’ combining a sharp critique of non-Muslim traditions with post-mortem testing and a non-eternal view of hell. By contrast, Ibn ʿArabī and Rūmī exhibit inclusivist and pluralising tendencies, especially in their doctrines of waḥdat al-wujūd (unity of beings) and divine mercy, while simultaneously upholding hierarchical evaluations of religions shaped by doctrinal commitments and historical circumstances. This internal tension challenges their frequent reception as straightforward paradigms of Islamic pluralism. The article concludes that Race’s grid is heuristically useful but historically fragile: exclusivism maps comparatively well onto medieval positions, whereas inclusivism and pluralism appear in mixed and unsystematic configurations. Accordingly, contemporary typologies can illuminate patterns of reasoning, but their application to premodern sources requires sustained methodological caution.